2001
DOI: 10.1902/jop.2001.72.8.1025
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Leukotriene B4 in Gingival Crevicular Fluid and Gingival Tissue in Specific Periodontal Diseases

Abstract: The results of the present study indicate that LTB4 is likely to be an important mediator in regulating inflammatory responses in the human periodontal tissues. This lipid mediator may play an important role in the pathophysiology of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
24
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 40 publications
9
24
0
2
Order By: Relevance
“…Considering the presence of LTB 4 in GCF and the increase in these levels with the degree of periodontal disease, our data support the previous findings that this lipid mediator is involved in the pathogenesis of periodontal disease 3,12 . The results of the present study showed an increase in GCF LTB 4 concentrations from periodontal health to disease.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Considering the presence of LTB 4 in GCF and the increase in these levels with the degree of periodontal disease, our data support the previous findings that this lipid mediator is involved in the pathogenesis of periodontal disease 3,12 . The results of the present study showed an increase in GCF LTB 4 concentrations from periodontal health to disease.…”
Section: Discussionsupporting
confidence: 91%
“…A greater concentration of LTB 4 was found in adult periodontitis sites compared to the non‐periodontitis sites. Emingil et al 3 reported higher concentrations of LTB 4 in subjects with CP compared to generalized aggressive periodontitis, localized aggressive periodontitis, gingivitis, and healthy groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations